The Association Between Cardiac Biomarker NT-proBNP and 30-Day Readmission or Mortality After Pediatric Congenital Heart Surgery. Issue 4 (July 2019) - Parker, Devin M.; Everett, Allen D.; Stabler, Meagan E.; Leyenaar, JoAnna; Vricella, Luca; Jacobs, Jeffrey P.; Thiessen-Philbrook, Heather; Parikh, Chirag; Greenberg, Jason; PhD, Jeremiah R. Brown
Background: Very little is known about clinical and biomarker predictors of readmissions following pediatric congenital heart surgery. The cardiac biomarker N-terminal pro-brain natriuretic peptide (NT-proBNP) can help predict readmission in adult populations, but the estimated utility in predicting risk of readmission or mortality after pediatric congenital heart surgery has not previously been studied. Our objective was to evaluate the association between pre- and postoperative serum biomarker levels and 30-day readmission or mortality for pediatric patients undergoing congenital heart surgery. Methods: We measured pre- and postoperative NT-proBNP levels in two prospective cohorts of 522 pediatric patients <18 years of age who underwent at least one congenital heart operation from 2010 to 2014. Blood samples were collected before and after surgery. We evaluated the association between pre- and postoperative NT-proBNP with readmission or mortality within 30 days of discharge, using multivariate logistic regression, adjusting for covariates based on the Society of Thoracic Surgeons (STS) Congenital Heart Surgery Mortality Risk Model. Results: The Johns Hopkins Children's Center cohort and the Translational Research Investigating Biomarker Endpoints in Acute Kidney Injury (TRIBE-AKI) cohort demonstrate event rates of 12.9% and 9.4%, respectively, for the composite end point. After adjustment for covariates in the STS congenital risk model, we did not find an association between elevated levels of NT-proBNP and increased risk of readmission or mortality following congenital heart surgery for either cohort. Conclusions: In our two cohorts, preoperative and postoperative values of NT-proBNP were not significantly associated with readmission or mortality following pediatric congenital heart surgery. These findings will inform future studies evaluating multimarker risk assessment models in the pediatric population.